Key to the world species of Holoparasitus Oudemans, 1936 (Acari: Parasitiformes: Parasitidae) - Witaliński, Wojciech (Zootaxa, 2017)
Keys to the world species of the mite genus Holoparasitus (Parasitidae family) are provided separately for males and females. The genus includes 55 species, 42 of which are allocated to eight species groups. The Holoparasitus inornatus species group is newly defined.